Attachment and addiction: theoretical framework and literature review - Sümer, Nebi; Oruçlular, Yasemin; Çapar, Tuğba (Journal of Dependence, 2015)
The review aims to understand the underlying dynamics of addiction from the perspective of attachment theory, which has been utilized as a framework in understanding the underpinnings of close relationships and emotion regulation in recent decades. First, explanations for dynamics of addiction with regard to attachment theory were discussed and then, 22 empirical studies investigating the relationship between attachment patterns and addictive behaviors were reviewed in a comprehensive table. Conceptually, dysfunctional emotion regulation strategies are the fundamental mediating processes linking insecure attachment to addiction. Secure attachment plays a protective role against addiction via effective emotion regulation strategies, whereas insecure attachment seems to be vulnerability factor for addiction via emotion and/or avoidance-focused emotion regulation strategies. Supporting this, reviewed empirical studies suggest that insecure attachment is a risk factor for addiction behaviors defined recently as an attachment disorder and affect regulation problem. Hyperactivating and deactivating emotion regulation strategies that underline attachment anxiety and avoidance dimensions, respectively, are proposed to create a tendency for addiction with different reasons. The proposed model based on attachment theory and reviewed work will provide a novel comprehensive framework for researchers and practitioners in understanding and coping with addiction.
Keywords: Anxious and avoidant attachment; addiction; emotion regulation strategies